Fluctuations of larval excretion in Strongyloides stercoralis infection - Uparanukraw P. (2014)
Follow-up stool examinations were carried out on two groups of the subjects who were screened negative (group 1) or positive (group 2) for Strongyloides stercoralis by the agar plate culture. This technique could detect S. stercoralis larvae in 87.5-96.4% of the subjects in group 2 and 0-5.9% of the subjects in group 1 on various days of the eight-week and four-week follow-up periods, respectively. The detection rate on each day of examination was not statistically different from that on the first day in both groups. Quantitative measurement of S. stercoralis larvae excreted in the feces of the subjects in group 2 by the standard direct smear method of Beaver and others revealed slight to marked fluctuations of the larval output in individual subjects. From the results of both stool examination methods, it could be implied that 52% of S. stercoralis-infected individuals had low-level infection.